Ground-Truthing Validation to Assess the Effect of Facility Locational Error on Cumulative Impacts Screening Tools. (31st August 2015) - Sadd, J. L.; Hall, E. S.; Pastor, M.; Morello-Frosch, R. A.; Lowe-Liang, D.; Hayes, J.; Swanson, C.
Abstract : Researchers and government regulators have developed numerous tools to screen areas and populations for cumulative impacts and vulnerability to environmental hazards and risk. These tools all rely on secondary data maintained by government agencies as part of the regulatory and permitting process. Stakeholders interested in cumulative impacts screening results have consistently questioned the accuracy and completeness of some of these datasets. In this study, three cumulative impacts screening tools used in California were compared, and ground-truth validation was used to determine the effect database inaccuracy. Ground-truthing showed substantial locational inaccuracy and error in hazardous facility databases and statewide air toxics emission inventories of up to 10 kilometers. These errors resulted in significant differences in cumulative impact screening scores generated by one screening tool, the Environmental Justice Screening Method.